Photodynamic therapy mediated by aluminium-phthalocyanine nanoemulsion eliminates primary tumors and pulmonary metastases in a murine 4T1 breast adenocarcinoma model - Rodrigues, Mosar Corrêa; Vieira, Lívia Gumieri; Horst, Frederíco Hillesheim; de Araújo, Eduarda Campos; Ganassin, Rayane; Merker, Carolin; Meyer, Thomas; Böttner, Julia; Venus, Tom; Longo, João Paulo F.; Chaves, Sacha Braun; Garcia, Mônica Pereira; et al. (Journal of photochemistry and photobiology. B, Biology, 2020)
Photodynamic therapy (PDT) is effective in the treatment of different types of cancer, such as basal cell carcinoma and other superficial cancers. However, improvements in photosensitizer delivery are still needed, and the use of PDT against more deeply located tumors has been the subject of many studies. Thus, the goal of this study was to evaluate the efficacy of a nanoemulsion containing aluminium-phthalocyanine (AlPc-NE) as a mediator of photodynamic therapy (PDT-AlPc-NE) against grafted 4T1 breast adenocarcinoma tumors in mice (BALB/c). Short after the appearance of the tumor, the animals were divided into groups (n = 5) as follows: untreated; only AlPc-NE and treated with PDT-AlPc-NE. The tumor volume was measured with a digital calliper at specific times. The presence of metastasis in the lungs was evaluated by microtomography and histopathological analyses. The results show that the application of PDT-AlPc-NE eradicated the transplanted tumors in all the treated animals, while the animals from control groups presented a robust increase in the tumor volume. Still more significantly, microtomography showed the animals submitted the PDT-AlPc-NE to be free of detectable metastasis in the lungs. The histological analysis of the lungs further confirmed the results verified by the microtomography. Therefore, this study suggests that PDT-AlPc-NE is effective in the elimination of experimentally grafted breast tumors in mice and also in preventing the formation of metastasis in the lungs. •Aluminium-phthalocyanine nanoemulsion (AlPc-NE) is readily internalized by murine breast adenocarcinoma 4T1 cells.•The AlPc-NE-mediated photodynamic therapy (PDT) shows nanomolar IC50 against 4T1 cells in vitro.•AlPc-NE-mediated PDT erradicated the primary 4T1 tumors and pulmonar metastases in BALB/c mice.